수분산계 기반 약물전달체 개발 및 에리스로마이신과 5-플루오로우라실의 효능 평가 - Seo, Hyo Won (The Graduate School, Ajou University, 2013)
A water dispersion system for the drug delivery can be divided into a hydrogel and a microemulsion containing certain amount of water. The hydrogel is a cross-linked structure of polymer with a large number of hydrophilic groups, pertaining a high affinity for water, making it an excellent biocompatible and biodegradable biopolymer. The microemulsion on the other hand is an isotropic mixture of transparent and stable form of oil, water, surfactant and cosurfactant. The water retaining properties of the microemulsion enhances the biocompatibility concomitantly with the absorption of the biopolymer. Therefore, the water dispersion system as biomaterial has been widely studied and used as a drug delivery system in tissue engineering and cell culture. In Chapter 2, we examined injectable in situ-forming gels as a localized drug delivery system. The effectiveness of systemically administered anticancer treatments is limited by difficulties in achieving therapeutic doses within tumors, a problem that is complicated by dose-limiting side effects to normal tissue. MCL acted as in vivo biodegradable drug depot over a defined experimental period. A single injection of 5-Fu-loaded MCL solution resulted in significant suppression of tumor growth, compared with repeated injection of free 5-Fu as well as saline and MCL alone. For both repeated injections of free 5-Fu and single injection of 5-Fu-loaded MCL, most of the 5-Fu was found in the tumor, indicating the maintenance of therapeutic concentrations of 5-Fu within the target tumor tissue and the prevention of systemic toxicity associated with 5-Fu in healthy normal tissues. In Chapter 3, The aim of this work was to prepare an erythromycin (EM) microemulsion (EM-microemulsion) for transdermal EM delivery using isotropic mixtures of oil and aqueous phases. Of all the EM-microemulsions prepared F-18 was the most suitable as it avoided precipitation and phase separation. The prepared EM-microemulsion is a white dispersion, with a suitable viscosity for transdermal delivery. In stability experiments, the EM-microemulsion showed no marked change in appearance for up to 3 weeks at 25 ℃. In accelerated stability experiments at 37 and 60 ℃, however, precipitated crystalline EM particles were observed in the EM-microemulsion. Diffusion of EM into the skin exhibited a first order release profile. Fluorescein (FL)-microemulsion penetrated to the dermis layer of skin. In conclusion, we confirmed that a water dispersion system of the prepared hydrogel and microemulsion are the possible effectively as drug delivery carriers. In Chapter 2, this work demonstrated that intratumoral injection of 5-Fu-loaded MCL may induce significant suppression of tumor growth through effective accumulation of 5-Fu in the tumor. In Chapter 3, we confirmed that EM-microemulsion could serve as an excellent transdermal carrier of EM.
학위논문(석사)아주대학교 일반대학원 :분자과학기술학과,2013. 8
Keywords: 약물전달